Experience of creation of the situation of controllable crisis in the developin - Y Sergeevna Lybimtseva (Peoples' Friendship University of Russia (RUDN University), 2010)
In this article the mechanism of subject formation of child's personality is investigated and the influence which pedagogic facilities of community of foster families exert upon this process. In this article the developing potential of controllable crisis situation is investigated and given proof, the significance of crisis situation in social adaptation of the personality, the stricture of crisis situation.